A Randomized Trial of Topical Fibrinogen-Depleted Human Platelet Lysate Treatment of Dry Eye Secondary to Chronic Graft-versus-Host Disease - Alan Sugar, MD; Munira Hussain, MS; Winston Chamberlain, MD, PhD; Reza Dana, MD; David Patrick Kelly, MD; Christopher Ta, MD; John Irvine, MD; Melissa Daluvoy, MD; Victor Perez, MD; Joshua Olson, MD; Vishal Jhanji, MD; Terence A. Walts, MBA; et al. (Ophthalmology Science, 2022)
Purpose: The purpose of the study was to evaluate, as a pilot trial, safety and tolerability of CAM-101 10% and 30% topical ophthalmic fibrinogen-depleted human platelet lysate (FD hPL) solution in patients with dry eye disease (DED) secondary to graft-versus-host disease (GvHD) after 6 weeks of treatment. Design: A phase I/II, pilot, prospective, multicenter, randomized, double-masked clinical trial. Participants: Patients with DED secondary to GvHD. Methods: Sixty-four adult patients were stratified by “symptom severity” (Ocular Surface Disease Index [OSDI], ocular discomfort Visual Analog Scale (VAS), ocular symptom frequency, and use of artificial tears) and then randomized 1:1:1 to CAM-101 (FD hPL) at 10% or 30% concentration or an electrolyte (Plasma-Lyte A) vehicle control, 1 drop in both eyes, 4 times daily, for 42 days. After 42 days, control patients were offered 42 days of open-label treatment with 30% FD hPL. Main Outcome Measures: Primary outcome safety measures were ocular and systemic adverse events and the number of patients in each group with clinically significant change from normal to abnormal in any ocular findings. Secondary outcomes were changes from baseline to day 42 in ocular discomfort, OSDI, fluorescein corneal staining, and lissamine green conjunctival staining relative to the vehicle control. The ocular symptom frequency was assessed on a 100-point VAS. Results: FD hPL 10% and 30% were safe and well tolerated. Relative to the vehicle control, significant decreases from baseline to day 42 were seen in the FD hPL 30% group with regard to ocular discomfort (mean decrease = −18.04; P = 0.018), frequency of burning/stinging (−20.23; P = 0.022), eye discomfort (−32.97; P < 0.001), eye dryness (−21.61; P = 0.020), pain (−15.12; P = 0.044), photophobia (−24.33; P = 0.0125), and grittiness (−20.08; P = 0.0185). Decreases were also seen for itching and foreign body sensation, though not statistically significant. Improvements were seen in tear breakup time (mean increase = 1.30 seconds; P = 0.082) and the investigator’s global evaluation 4-point scale (mean decrease = −0.86; P = 0.026). Corneal fluorescein staining was not improved. The OSDI had a mean decrease of −8.88 compared to the vehicle, although not statistically significant. Conclusions: Fibrinogen-depleted human platelet lysate appears to be well tolerated, with no significant toxicity at concentrations of 10% and 30%. These initial data suggest some efficacy, especially for subjective outcome measures relative to baseline assessments and treatment with the vehicle, but larger studies are needed to confirm these effects.